Proceedings of the 33rd Annual ACM Conference on Human Factors in Computing Systems 2015
DOI: 10.1145/2702123.2702445
|View full text |Cite
|
Sign up to set email alerts
|

Inferring Employee Engagement from Social Media

Abstract: Employees increasingly are expressing ideas and feelings through enterprise social media. Recent work in CHI and CSCW has applied linguistic analysis towards understanding employee experiences. In this paper, we apply dictionary based linguistic analysis to measure 'Employee Engagement'. Employee engagement is a measure of employee willingness to apply discretionary effort towards organizational goals, and plays an important role in organizational outcomes such as financial or operational results. Organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(6 citation statements)
references
References 42 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…The notion of additional work as meaningful is one that has been raised in previous research, e.g. when employees choose to contribute free labour as a demonstration of engagement with an organisation [41], yet it has not previously been tied to the arena of relationships. Our data suggested that effort was highly valued when it was perceived as going beyond basic relational expectations.…”
Section: Discretionary Investmentmentioning
confidence: 99%
“…The notion of additional work as meaningful is one that has been raised in previous research, e.g. when employees choose to contribute free labour as a demonstration of engagement with an organisation [41], yet it has not previously been tied to the arena of relationships. Our data suggested that effort was highly valued when it was perceived as going beyond basic relational expectations.…”
Section: Discretionary Investmentmentioning
confidence: 99%
“…Machine Learning (Video, Audio, Text) (Angrave et al, 2016;McIver et al, 2018;Shami et al, 2015); (Fecheyr-Lippens et al, 2015;Silvestre et al, 2015)…”
Section: Appendixmentioning
confidence: 99%
“…Research shows that emphasis on social themes and efforts while connecting with other individuals causes stronger social and collaborative relationships among groups trying to achieve common objectives [40]. Collaborative actions in the context of policing can increase social cohesion and reduce safety concerns among citizens [25].…”
Section: Social Interactionsmentioning
confidence: 99%